2010
DOI: 10.1016/j.pain.2010.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Neural bases of conditioned placebo analgesia

Abstract: Despite growing interest in the placebo effect, the neural correlates of conditioned analgesia are still incompletely understood. We investigated herein on brain activity during the conditioning and post-conditioning phases of a placebo experimental paradigm, using event-related fMRI in 31 healthy volunteers. Brief laser heat stimuli delivered to one foot (either right or left) were preceded by different visual cues, signalling either painful stimuli alone, or painful stimuli accompanied by a (sham) analgesic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 52 publications
6
92
0
2
Order By: Relevance
“…The prefrontal cortex seems to play a crucial role in this mechanism. Activity in the dorsolateral prefrontal cortex was found in the period preceding noxious stimulation, which correlated with activity in the PAG and the subsequent placebo analgesic response (Wager et al, 2004;Eippert et al, 2009a;Lui et al, 2010). Intriguingly, both temporary functional lesions in the prefrontal cortex by repetitive transcranial magnetic stimulation (Krummenacher et al, 2010) as well as degenerated and disconnected frontal lobes in Alzheimer's disease (Benedetti et al, 2006) are associated with a reduction in or complete loss of verbally induced placebo analgesic responses.…”
Section: A Painmentioning
confidence: 92%
See 1 more Smart Citation
“…The prefrontal cortex seems to play a crucial role in this mechanism. Activity in the dorsolateral prefrontal cortex was found in the period preceding noxious stimulation, which correlated with activity in the PAG and the subsequent placebo analgesic response (Wager et al, 2004;Eippert et al, 2009a;Lui et al, 2010). Intriguingly, both temporary functional lesions in the prefrontal cortex by repetitive transcranial magnetic stimulation (Krummenacher et al, 2010) as well as degenerated and disconnected frontal lobes in Alzheimer's disease (Benedetti et al, 2006) are associated with a reduction in or complete loss of verbally induced placebo analgesic responses.…”
Section: A Painmentioning
confidence: 92%
“…The majority of neuroimaging studies addressing placebo analgesia report that the reduced pain ratings during placebo analgesia are accompanied by decreased activity in the classic pain-processing areas, including the thalamus, insula, somatosensory cortex, and mid-cingulate regions (Wager et al, 2004;Bingel et al, 2006;Eippert et al, 2009a;Lui et al, 2010;Elsenbruch et al, 2012a; (Fig. 4).…”
Section: A Painmentioning
confidence: 99%
“…Lui et al [61] found that brain activities overlapped in the right dorsolateral prefrontal cortex when healthy subjects expected analgesia (i.e. anticipatory phase of CSs), experienced analgesic effects (i.e.…”
Section: Conditioning and Prior Experience (A) Classical Conditioningmentioning
confidence: 99%
“…Although the dopamine findings and the electrophysiological data were obtained in different studies (de la Fuente-Ferná ndez et al, 2001, it is tempting to speculate that the changes in firing pattern of the subthalamic and thalamic neurons were triggered by dopamine release. Modern brain imaging techniques have been fundamental in the understanding of the placebo response, particularly placebo analgesia, and many brain imaging studies have been carried out to describe the functional neuroanatomy of the placebo analgesic effect (e.g., Bingel et al, 2006;Eippert et al, 2009aEippert et al, , 2009bHashmi et al, 2012;Kong et al, 2006Kong et al, , 2007Lui et al, 2010;Meissner et al, 2011;Petrovic et al, 2002;Price et al, 2007Price et al, , 2009Scott et al, 2007Scott et al, , 2008Tracey, 2010;Wager et al, 2004Wager et al, , 2007Wager et al, , 2011Zubieta et al, 2005). A meta-analysis of brain imaging data using the activation likelihood estimation method identified two phases: the expectation phase of analgesia and the pain inhibition phase (Amanzio et al, 2013).…”
Section: Introductionmentioning
confidence: 99%